Entrepreneurship and economic development in Hong Kong - Yu, Fu-Lai Tony, 1950- (Routledge advances in Asia-Pacific business, 1997)
This is the first systematic economic study of the nature, operation and contribution of entrepreneurship to the growth of Hong Kong. The author argues that the success of Hong Kong is due to adaptive entrepreneurship.